Community structure, diversity and function of endophytic and soil microorganisms in boreal forest - Luo, Xi; Yan, Guoyong; Wang, Qinggui; Xing, Yajuan (Frontiers in Microbiology, 2024)
Despite extensive studies on soil microbial community structure and functions, the significance of plant-associated microorganisms, especially endophytes, has been overlooked. To comprehensively anticipate future changes in forest ecosystem function under future climate change scenarios, it is imperative to gain a thorough understanding of the community structure, diversity, and function of both plant-associated microorganisms and soil microorganisms. In our study, we aimed to elucidate the structure, diversity, and function of leaf endophytes, root endophytes, rhizosphere, and soil microbial communities in aborealboreal forest. Our findings revealed significant differences in the community structure and diversity of fungi and bacteria across leaves, roots, rhizosphere, and soil. Notably, we observed that the endophytic fungal or bacterial communities associated with plants comprised many species distinct from those found in the soil microbial communities, challenging the assumption that most of endophytic fungal or bacterial species in plants originate from the soil. Furthermore, our results indicated noteworthy differences in the composition functional groups of bacteria or fungi within leaf endophytes, root endophytes, rhizosphere, and soil, suggesting distinct roles played by microbial communities in plants and soil. These findings underscore the importance of recognizing the diverse functions performed by microbial communities in both plant and soil environments. In conclusion, our study emphasizes the necessity of a comprehensive understanding of the structure and function microbial communities in both plants and soil for assessing the functions of boreal forest ecosystems.